Grammar-based systems: definition and examples - Mernik, Marjan (Informatica (Ljubljana), 2004)
Formal language theory is an important part of theoretical computer science and has also been applied in many practical applications. The importance of context-free grammars and attribute grammars for compiler construction and automatic generation for compilers/interpreters is already well known. However, grammars can be found in many other applications which are not as clearly related to their original application - language description and implementation. We call such systems grammar-based systems. No general comparison and classification has been done until now despite these systems having existed for a long time. The aim of this paper is to introduce and popularize grammar-based systems.
Keywords: računalniški sistemi; sintaksa; slovnica; grammar; algoritmi